2008
DOI: 10.1007/s11081-008-9036-4
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective aerodynamic shape optimization for unsteady viscous flows

Abstract: This paper presents an adjoint method for the multi-objective aerodynamic shape optimization of unsteady viscous flows. The goal is to introduce a Mach number variation into the Non-Linear Frequency Domain (NLFD) method and implement a novel approach to present a time-varying cost function through a multi-objective adjoint boundary condition. The paper presents the complete formulation of the time dependent optimal design problem. The approach is firstly demonstrated for the redesign of a helicopter rotor blad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…During the unsteady evolution, the airfoil surface is moving with time, and the dynamic grid technique is introduced in the grid generation to improve the computational efficiency (Ying et al, 2011). Nadarajah and Tatossian (2008) also have presented an adjoint method for the multi-objective aerodynamic shape optimization of unsteady viscous flows. Their method is beneficial when both the pitching angle and free stream Mach number are sinusoidally varied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the unsteady evolution, the airfoil surface is moving with time, and the dynamic grid technique is introduced in the grid generation to improve the computational efficiency (Ying et al, 2011). Nadarajah and Tatossian (2008) also have presented an adjoint method for the multi-objective aerodynamic shape optimization of unsteady viscous flows. Their method is beneficial when both the pitching angle and free stream Mach number are sinusoidally varied.…”
Section: Introductionmentioning
confidence: 99%
“…Their method is beneficial when both the pitching angle and free stream Mach number are sinusoidally varied. They showed that the multi-objective cost function was able to preserve both the lift and pitching moment while simultaneously decreasing the overall drag (Nadarajah and Tatossian, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Aircraft configurations may be studied through multidisciplinary design optimization that takes into account both the flow and the structure [45,28,24]. The adjoint method has also extended to rotorcraft [29,12,30] and turbomachinery [56,34,57] design optimization.…”
Section: Numerical Optimizationmentioning
confidence: 99%
“…Once the shape and aerodynamic characteristics of a rotor are defined, that is, solidity, pitch angle, lift, and drag coefficients, the BEMT equation (1) yields the induced velocity radial distribution, A/(x), and using equations (3), (4), and (5) the global coefficients CT, CQ^, and CQ" are computed.…”
Section: Blade Element Momentum Theorymentioning
confidence: 99%